RADIKALISME DALAM PERSPEKTIF ILMU PSIKOLOGI AGAMA - Octavia Fauziah F; Agil Syauqi Rabbi Maulana Bahri; Nurul Hidayatur Rohmah; Mufarrohatul Jamila (STAINU Purworejo, 2021)
Abstract At present, the world is again in shock with the emergence of violent issues which are allegedly originating from radical movements. Violence occurs because of political, economic, or religious conflicts. This study uses a type of library research. Psychology of religion as a branch of psychology has a very important role in explaining the motivation of religious violence carried out by a group of people who use religion as an inspiration and efforts to prevent it, including how to change someone who is even a radical person to be no longer involved in radicalism. Keywords : radicalism, psychology, religion Abstrak Saat ini, dunia kembali digemparkan dengan munculnya isu-isu kekerasan yang disinyalir berasal dari gerakan-gerakan radikal. Kekerasan terjadi karena adanya konflik politik, ekonomi, maupun lembaga tertentu dari agama. Penelitian ini menggunakan jenis penelitian kepustakaan. Psikologi agama sebagai salah satu cabang dari ilmu psikologi, memiliki peran yang begitu penting dalam menjelaskan motivasi kekerasan keagamaan yang dilaksanakan oleh sekelompok orang yang menggunakan agama sebagai inspirasi dan usaha dalam mencegahnya, termasuk bagaimana cara mengubah seseorang yang radikal sekali pun menjadi tidak lagi terlibat dalam radikalisme. Kata Kunci : radikalisme, psikologi, agama